Prevalence, types, and determinants of intimate-partner violence among pregnant women in Northern Uganda: a hospital-based cross-sectional study - Okot, Jerom; Anena, Cinderella; Okema, Nelson James; Amuku, Denis Oryem; Otunnu, Jerry Enock; oweka, Beatrice Lamwaka; Lutara, Ian Daniel; Watum, Francis; Nsubuga, Yakobo; Bongomin, Felix; Pebolo, Pebalo Francis; Ouma, Simple (BMC public health, 2025)
Background Intimate partner violence (IPV) against women is a global health issue, affecting one in three women worldwide. Exposure to IPV during pregnancy poses significant health risks to the mother and her foetus, leading to various complications. This study aimed to determine the prevalence, types, and determinants of IPV among pregnant women in Northern Uganda. Methods A cross-sectional study was conducted at Gulu Regional Referral Hospital’s antenatal care clinic from June to August 2023. Data were collected using semi-structured questionnaires in English or Acholi. Participants were selected through systematic random sampling. Information on socio-demographic characteristics, partner attributes, and IPV exposure was collected. Descriptive statistics and modified Poisson regression analyses were performed using STATA 18.0. Associations between variables and IPV were reported as adjusted prevalence ratios (aPR), with p < 0.05 considered statistically significant. Results Among the 339 participants, the mean age (standard deviation) was 26.1(5.5) years. Overall, 73.2% ( n = 248) of the participants were exposed to IPV in pregnancy. The most common form of IPV was controlling behaviour by male partners (61.9%, n = 210), followed by emotional violence (34.8%, n = 118), economic violence (29.5%, n = 100), sexual violence (28.9%, n = 98), and physical violence (16.2%, n = 55). Factors associated with IPV included being in a polygynous marriage (aPR: 1.2, 95% CI: 1.03–1.31, p = 0.013), having poor (aPR: 1.6, 95% CI: 1.32–1.89, p < 0.0001) or good (aPR: 1.2, 95% CI: 1.03–1.51, p = 0.026) versus perfect relationship with the husband’s family, week of amenorrhea (aPR: 1.01, 95% CI: 1.003–1.02, p = 0.006), and maternal age (aPR: 0.98, 95% CI: 0.97–0.99, p = 0.003). Conclusions IPV during pregnancy, particularly controlling behaviour by male partners, is highly prevalent in Northern Uganda. To mitigate the negative impacts on maternal and foetal health, targeted interventions by the Ministry of Health, development partners, and other stakeholders are urgently needed to prevent and manage IPV in pregnancy.